Abhivyakti media for development : about us - Arvind Chitte (2008)
'Abhivyakti' is expression. For us, Abhivyakti has been a resultant stage in the natural progression of our involvement and experience with media. All of us have a social work orientation and most hold degrees from reputed institutions. We have used media as a means for education, for motivation, in our spheres of activity. This usage has also extended to experiments with media with rural segments of society. These varied experiences, shared cumulatively have given us insights related to the potential of the media as a contributing and catalytic means to the process of growth. Herein as a seed thought, we felt the paucity of relevant material for development-oriented work.